Limitations on the Detection Rate of High-Risk HPV by Hybrid Capture 2 Methodology in High Grade Intraepithelial (HSIL) or Atypical Squamous Cells-Cannot Exclude HSIL (ASC-H) Cytological Lesions with Proved CIN2+ - Jean-Christophe Noël; Philippe Simon (Analytical Cellular Pathology)
Recent literature data suggest that the high-risk human papillomaviruses (HR-HPVs) testing with several molecular techniques could be an alternative to cytology in the detection of cervical intraepithelial neoplasias of grade 2 or worse (CIN2+). However, any molecular techniques have its own limits and may give false negative results which must be clearly known before undertaking a primary HPV screening. This study aims to evaluate the performance of the high-risk HPV hybrid capture II detection kit (HCII) which is considered as a “gold standard technique” in a series of 100 women having proved both cytological lesions of atypical squamous cells-cannot exclude an HSIL (ASC-H) or high-grade squamous intraepithelial lesion (HSIL) and histological lesions of CIN2+. The clinical sensitivity of HCII in women with a cytological diagnosis of ASC-H/HSIL and a diagnosis of CIN2+ is high but not absolute and estimated at 96% (95,6% and 100% of women with a diagnosis of CIN2/3 or invasive squamous cell carcinoma, resp.). These data although they are infrequent must be clearly referred before to start an HPV primary screening of CIN2+ especially with HCII methodology.